Comparative Study of Anemia of Inflammation in Pregnant and Non-Pregnant Women - Fakharunisasa, Qamarunissa Muhabbat, Zaheer, Sumaya, Sajida Muneer, Waqarunissa Ahmed (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To compare the prevalence of Anemia of Inflammation (AI) in pregnant and Non-pregnant women. Study design: A Cross sectional study. Place and duration of study: Indus Medical College, Tando Muhammad Khan, between the duration of January 2021 to November 2021 Methodology: A total of 300 participants were enrolled for this study which comprises of 133 pregnant and 167 non-pregnant women. Pregnant women between 7th to 13th weeks of gestation were selected with hemoglobin and serum ferritin level less than 10 g/dL. Different hematological parameters were analyzed to assess the prevalence of AI in anemic pregnant and non-pregnant women which include Hemoglobin (Hb), Red Blood Cells (RBCs), hematocrit (HCT), Mean Corpuscular Volume (MCV), Hepcidin, Total Serum Iron (TSI), Transferrin, Serum Ferritin (sFtn) and Soluble transferrin receptor (sTfR). Results: Our data indicates that, AI was most prevalent in women with child bearing age, about 17% pregnant and 23% non-pregnant women were associated with β-thalassemia which could be a reason of anemia of inflammation. High level of Hepcidin, transferrin saturation and serum ferritin were observed in our participants that indicates the presence of AI in our study population. Conclusions: In our study, the prevalence of AI were high in women with chronic inflammation in comparison to women without subsequent infection. The proper diagnosis is necessary for the management and better treatment of AI in pregnant women.